The limits of competing interest disclosures - Bero, L (BMJ Group, 2005)
Objective: To assess the effectiveness of conflict of interest disclosure policies by comparing a competing interests disclosure statement that met the requirements established by the journal in a 2003 article on health effects of secondhand smoke based on the American Cancer Society CPS-I dataset with internal tobacco industry documents describing financial ties between the tobacco industry and authors of the study. Design: Descriptive analysis of internal tobacco industry documents retrieved from the Legacy Tobacco Documents Library, University of California, San Francisco. Results: Meeting the requirements for financial disclosure established by the journal did not provide the reader with a full picture of the tobacco industry's involvement with the study authors. The tobacco industry documents reveal that the authors had long standing financial and other working relationships with the tobacco industry. Conclusion: These findings are another example of how simply requiring authors to disclose financial ties with the tobacco industry may not be adequate to give readers (and reviewers) a full picture of the author's relationship with the tobacco industry. The documents also reveal that the industry funds research to enhance its credibility and endeavours to work with respected scientists to advance its goals. These findings question the adequacy of current journal policies regarding competing interest disclosures and the acceptability of tobacco industry funding for academic research.